(untitled) (UNED Research Journal, 2020)
Introduction: Muskmelon is among Costa Rica’s main agricultural export products, and selection parameters for yield, considering direct and indirect effects, are best studied by path coefficient analysis, which divides correlation coefficients into direct and indirect effect components. Objective: To obtain a Path analysis for greenhouse Muskmelon yield. Methods: we planted the specimens on coconut fiber as substrate, managed with fertigation. The variables were: days to start of harvest (days after transplant-dat), fruit weight (FW, in g), number of fruits per plant (NFP), yield (kg/plant), fruit flesh firmness (N), percentage of total soluble solids (°Brix), equatorial fruit diameter (ED, in mm), polar fruit diameter (PD, in mm), PD/ED ratio, fruit flesh thickness (FFT, in mm), fruit cavity thickness (FCT, in mm), and 2FFT/FCT ratio. Results: Yield showed a positive and highly significant correlation with NFP (r=0,97**), PD/ED ratio (r=0,65**) and PD (r=0,54**). The main positive direct effects on yield were exhibited by NFP (path coefficient-PC=1,05), FW (PC=0,20), PD (PC=0,16), 2FFT/FCT ratio (PC=0,11) and FCT (PC=0,06), while maximum positive indirect effects on yield were exhibited by PD/ED ratio (PC=0,69) and PD (PC=0,48) through NFP. The main negative direct effects on yield were exhibited by PD/ED ratio (PC=-0,19), FFT (PC=-0,15) and ED (PC=-0,05). Conclusion: Under these conditions, number of fruits per plant was the main yield contributing variable.